Avaliação de perdas aparentes de água potável por erros de medição em hidrômetros de economias da Grande Vitória-ES - Aguiar, Ludmila Costa de (2019)
In Brazil, the average water loss rate in water supply systems is approximately 38%. Water Losses are formed by the real and apparent losses. Real losses are characterized by water dissipation in the system. Apparent losses are represented by billing losses. There is a great need for new investments in the area, to expand coverage and improve existing systems, highlighting the importance of searching for efficient use of available resources. Increased control of water distribution contributes to minimizing losses. Within the apparent loss share, there are losses that occur due to metering errors. Given this, there is a need to ensure that the performance of water meters are reaching appropriate levels. This paper presents the results of INMETRO (Brazilian metrology institute) methodology applications for meter error evaluation. Identifying and quantifying losses is an essential initiative for the implementation of actions to control and reduce water losses. The methodology proposed by ABNT is also applied for the quantification of losses due to metering errors. The data were provided by CESAN, from the Greater Vitoria metropolitan region, and the water meter tests were performed in an INMETRO-certified water meter laboratory. The results allow to conclude that the wear of the meters exists, is relevant, and the study discussions corroborate this statement. When evaluating the tendency of the park's measurement performance to decrease, the relationship between the performance and age variables can be noticed. The use of loss estimation methods to aid management and control in the supply system allows for tangible losses and contributes to the evolution of park management.